Executive presence : the missing link between merit and success - Hewlett, Sylvia Ann, 1946- (Harper Business, an imprint of HarperCollinsPublishers, 2014)
"Are you "leadership material?" More importantly, do others perceive you to be? Sylvia Ann Hewlett, a noted expert on workplace power and influence, shows you how to identify and embody the Executive Presence (EP) that you need to succeed. You can have the experience and qualifications of a leader, but without executive presence, you won't advance. EP is an amalgam of qualities that true leaders exude, a presence that telegraphs you're in charge or deserve to be. Articulating those qualities isn't easy, however. Based on a nationwide survey of college graduates working across a range of sectors and occupations, Sylvia Hewlett and the Center for Talent Innovation discovered that EP is a dynamic, cohesive mix of appearance, communication, and gravitas. While these elements are not equal, to have true EP, you must know how to use all of them to your advantage. Filled with eye-opening insights, analysis, and practical advice for both men and women, mixed with illustrative examples from executives learning to use the EP, Executive Presence will help you make the leap from working like an executive to feeling like an executive."--Publisher's description.